Odorant Binding Proteins of the Desert Locust Schistocerca gregaria (Orthoptera, Acrididae): Topographic Expression Patterns in the Antennae - Jiang, Xingcong; Ryl, Miriam; Krieger, Jürgen; Breer, Heinz; Pregitzer, Pablo (Frontiers in Physiology, 2018)
Odorant binding proteins (OBPs) enriched in the sensillum lymph are instrumental in facilitating the transfer of odorous molecules to the responsive receptors. In Orthopteran locust species, an in-depth understanding of this important soluble protein family is still elusive. In a previous study, we have demonstrated that the repertoire of locust OBPs can be divided into four major clades (I–IV) on the phylogenetic scale and for representatives of subfamily I-A and II-A a distinct sensilla-specific expression pattern was determined. In this study, by focusing on a representative locust species, the desert locust Schistocerca gregaria, we have explored the antennal topographic expression for representative OBPs of other subfamilies. First, subtypes of subfamily III-A and III-B were exclusively found in sensilla chaetica. Then, a similar expression pattern in this sensillum type was observed for subfamily I-B subtypes, but with a distinct OBP that was expressed in sensilla coeloconica additionally. Moreover, the atypical OBP subtype from subfamily IV-A was expressed in a subpopulation of sensilla coeloconica. Last, the plus-C type-B OBP subtype from subfamily IV-B seems to be associated with all four antennal sensillum types. These results profile diversified sensilla-specific expression patterns of the desert locust OBPs from different subfamilies and complex co-localization phenotypes of distinct OBP subtypes in defined sensilla, which provide informative clues concerning their possible functional mode as well as a potential interplay among OBP partners within a sensillum.